Optimasi Natrium Alginat Dan Kalsium Klorida (Cacl2) Sebagai Agen Sambung Silang Nanopartikel Ekstrak Etanol Daun Katuk (Sauropus Androgynus (L.) Merr) - Akhmad Ngafif (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2020)
Obesity is defined as a condition with abnormal or excessive fat accumulation in adipose tissue so that it can interfere with health. The increasing prevalence of obesity was a major health problem worldwide. One effort to prevent obesity can be done by utilizing natural materials in Indonesia, including katuk leaves (Sauropus androgynus (L.) Merr). Katuk leaves contain kaempferol compounds which had the effect of reducing body fat or antiobesity. The nanoparticle formulation of katuk leaf ethanol extract made using a polymer of sodium alginate and calcium chloride (CaCl2) as a crosslinking agent. This study aims to determine the effect of the use of sodium alginate and calcium chloride (CaCl2) on physical characteristics in nanoparticle extracts of katuk leaf ethanol, and determine the nanoparticle formula with optimal physical characteristics. Optimized parameters were visual, transmittance, adsorption efficiency, particle size distribution, polydispersity index, zeta potential and particle morphology in the optimal formula of katuk leaf ethanol extract nanoparticles. Based on Design Expert 10.0.1 with the factorial design method, the optimal formula is obtained with a ratio of sodium alginate and calcium chloride (CaCl2) of 0.102%: 0.010%. Visual prediction results obtained 3 (clear); transmitting 90.66% and absorption efficiency 81.1359%. The t-test results showed that these observations differed insignificantly to the results of the predictions indicating that the equation of each optimization parameter was valid. The optimal formula had 66.4% units 54.59 nm of size nanoparticles and 33.6% units 440.1 nm, 0.465 of polydispersity index, -17.6 mV of zeta potential and particle morphology with a non-spherical shape in a loose aggregate.